Analysis of TRPV channel activation by stimulation of FC[epsilon]RI and MRGPR receptors in mouse peritoneal mast cells - Solís López, Alejandra; Kriebs, Ulrich; Marx, Alexander; Freichel, Marc; Tsvilovskyy, Volodymyr (PLOS ONE, 2017)
The activation of mast cells (MC) is part of the innate and adaptive immune responses and depends on Ca2+ entry across the plasma membrane, leading to the release of preformed inflammatory mediators by degranulation or by de novo synthesis. The calcium conducting channels of the TRPV family, known by their thermo and osmotic sensitivity, have been proposed to be involved in the MC activation in murine, rat, and human mast cell models. So far, immortalized mast cell lines and nonspecific TRPV blockers have been employed to characterize the role of TRPV channels in MC. The aim of this work was to elucidate the physiological role of TRPV channels by using primary peritoneal mast cells (PMCs), a model of connective tissue type mast cells. Our RT-PCR and NanoString analysis identified the expression of TRPV1, TRPV2, and TRPV4 channels in PMCs. For determination of the functional role of the expressed TRPV channels we performed measurements of intracellular free Ca2+ concentrations and beta-hexosaminidase release in PMCs obtained from wild type and mice deficient for corresponding TRPV1, TRPV2 and TRPV4 in response to various receptor-mediated and physical stimuli. Furthermore, substances known as activators of corresponding TRPV-channels were also tested using these assays. Our results demonstrate that TRPV1, TRPV2, and TRPV4 do not participate in activation pathways triggered by activation of the high-affinity receptors for IgE (FcεRI), Mrgprb2 receptor, or Endothelin-1 receptor nor by heat or osmotic stimulation in mouse PMCs.
Gesehen am 19.07.2018
Im Titel ist [epsilon] als griechischer Buchstabe dargestellt